2019
DOI: 10.3844/ajbbsp.2019.23.32
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Aging in Yeast Saccharomyces cerevisiae by Roselle Petal Extract (Hibiscus sabdariffa L.)

Abstract: Cellular aging drives diseases. Free radicals are called the main cause of cellular aging. Antioxidants can protect the body from free radical attack by reducing its negative effects. An antioxidant source can be obtained from plants, such as roselle (Hibiscus sabdariffa. L). This research was conducted to analyze the ability of roselle petals extract to increase the life span of model organisms Saccharomyces cerevisiae BY4741. The IC 50 value of extract-derived antioxidant activity based on DPPH and ABTS assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
(38 reference statements)
1
12
0
2
Order By: Relevance
“…Our data suggest that clove leaf extract could promote oxidative stress tolerance in yeast cells. Other extracts that are capable of inducing oxidative stress tolerance response in yeast are green tea extract [29], Red chicory leaf [30], Tinospora cordifolia [31], and roselle petal [32].…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest that clove leaf extract could promote oxidative stress tolerance in yeast cells. Other extracts that are capable of inducing oxidative stress tolerance response in yeast are green tea extract [29], Red chicory leaf [30], Tinospora cordifolia [31], and roselle petal [32].…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicated that the plant extracts/fractions induced the capability of yeast cells to cope with strong oxidative stress conditions. Previous studies revealed the potential of various extracts of plants, including rosella and clove, in promoting yeast viability in oxidative stress conditions [ 25 , 33 ]. The particular extract with such antioxidant activities may be developed as an antiaging agent.…”
Section: Resultsmentioning
confidence: 99%
“…Low glucose in the positive control is considered as calorie restriction (CR) conditions. Such CR condition will induce yeast cellular mechanisms including mitochondrial activity response to oxidative stress and autophagy, which contribute to the yeast lifespan extension (Roux et al, 2010;Sarima et al, 2019). Each culture was incubated for 11 th -days where a spot test was conducted at days 7 and 11 of incubations.…”
Section: Aging Assaymentioning
confidence: 99%
“…The procedure was performed according to the previous study by using Rhodamine B as a probe (Sarima et al, 2019). The yeast was incubated in liquid YES medium supplemented with phytoextracts of X. granatum and Xyloccensins K at the best concentration during the aging assay.…”
Section: Active Mitochondrial Stainingmentioning
confidence: 99%